(untitled) (Research, Society and Development, 2020)
This essay proposes a reflection on the transformations that occurred in the legislation protecting children and youth and their implementation in the day-to-day of care entities for children and adolescents at risk. Through the reorganization proposed by the Child and Adolescent Statute – ECA (Law 8.069/1990), changes began to take place, including a focus on the recognition of childhood, and also emphasizing family and community coexistence as a fundamental right. Seeking to guide practices, stands out the social assistance policy, a non-contributory social security policy of the State, which aims to guarantee individuals, families and social groups the survival, acceptance and familiarity of the community and through programs, projects, services and social protection benefits, hierarchical in basic protection and special protection.